KERAGAMAN JAMUR GANODERMA PADA POHON PENEDUH DI SLEMAN, YOGYAKARTA - Maryono, Tri (Jurnal Hutan Tropis, 2024)
Shade trees are part of urban forest plants that function as cooling, windbreaks, noise reducing, pollutants absorbing, and beautifying the city. Ganoderma is a fungus that causes death and damage to shade trees. This survey aims to determine the presence of Ganoderma on shade plants in Sleman, Yogyakarta. The survey was carried out in Depok and Ngaglik Subdistricts, Sleman Regency. The results of the survey obtained were Ganoderma fruit bodies on dead or stump trees. Two Ganoderma fruit bodies were found on angsana trees and stumps, one Ganoderma was found on johar tree, ketapang stumps, and on unknown wood species. Fruiting body Ganoderma characters vary in shape and color, stiped and not stiped, laccate and not laccate. The different morphological characters of the fruiting bodies are thought to be due to differences in species.